Management of Microbial Resources in the Environment - Malik, Abdul.; Grohmann, Elisabeth.; Alves, Madalena. (Springer Netherlands : Imprint: Springer, 2013)
This volume details the exploration, collection, characterization, evaluation and conservation of microbes for sustainable utilization in the development of the global as well as national economies, e.g. in agriculture, ecosystems, environments, industry and medicine. Many research institutes and universities all over the world carry out microbiological and biotechnological research, which generates substantial genomic resources such as cDNA libraries, gene constructs, promoter regions, transgenes and more valuable assets for gene discovery and transgenic product development. This work provides up-to-date information on the management of microbial resources in the environment. It also covers the ecology of microorganisms in natural and engineered environments. In trying to understand microbial interactions it further focuses on genomic, metagenomic and molecular advances, as well as on microbial diversity and phylogeny; ecological studies of human, animal and plant microbiology and disease; microbial processes and interactions in the environment; and key technological advances. Though not intended to serve as an encyclopedic review of the subject, the various chapters investigate both theoretical and practical aspects and provide essential basic information for future research to support continued development.